Strategi Promosi Identitas Baru Hotel Kristal Kupang menjadi Hotel Swiss-Belinn Kristal Kupang melalui Media Relations - Tamara Yuchi Marrend Halundaka; Mas'amah Mas'amah; Yohanes K. N. Liliweri (Universitas Nusa Cendana, 2019)
Hotel Kristal is the first hotel in Kota Kupang with the first 3-star standard. The increasing development of the hotel business made the owner of Kristal Hotel switch management to Swiss-Belhotel International. Changes in hotel management include the creation of a new corporate identity and require a promotion to be known, recognized and can be a reference when wanting to use hotel services, with a promotional strategy to promote a new corporate identity to the public through media relations. This study aims to find out what media relations are used in promotions and obstacles and solutions. The type of research used is qualitative research with descriptive methods. The data in this study were collected through interviews, observation, and documentation study techniques. The results of the study show that the press luncheon and press gathering are media relations activities which are one of the promotional strategies used in promoting the identity of Swiss-Belinn Kristal Kupang. In promoting a new corporate identity, the company encounters obstacles, namely the high-budget advertising budget, through this obstacle, the company can overcome it by utilizing the company's social media as a forum for promotion, without reducing relations with local media. It is hoped that through this research Swiss-Belinn Kristal Kupang Hotel can maintain its existence by expanding the reach of relations with the media, and can make identity as an asset to maintain and increase business value.